2019
DOI: 10.14202/vetworld.2019.998-1007
|View full text |Cite
|
Sign up to set email alerts
|

Variabilities of hydatidosis in domestic animals slaughtered at Cairo and Giza abattoirs, Egypt

Abstract: Aim: The effect of some variables on hydatidosis in animals slaughtered at Cairo and Giza abattoirs was investigated and the influence on serum biochemical parameters, antioxidant enzymes, and histopathological lesions caused by these parasites as a consequence was estimated. Materials and Methods: The effect of some variables on hydatidosis in 397 sheep, 401 cattle, 435 buffaloes, and 341 camels slaughtered at Cairo and Giza abattoirs was investigated, and the influence on serum biochemical parameters, antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
4
11
0
Order By: Relevance
“…Furthermore, the present data illustrate the occurrence of hydatid cysts in aged cattle at a rate of 2.6% (5 infected out of 175 examined animals), while no infection was detected among young cattle (<5 years of age) ( N = 400). The present findings agree with several previous studies performed either at the national (Egypt) or international level ( 70 , 78 , 79 ). This observation could be attributed to the fact that older animals are exposed to infection more than young ones and aged animals get slaughtered more than young ages, since their production (calves/milk) and working capacity decrease ( 80 ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Furthermore, the present data illustrate the occurrence of hydatid cysts in aged cattle at a rate of 2.6% (5 infected out of 175 examined animals), while no infection was detected among young cattle (<5 years of age) ( N = 400). The present findings agree with several previous studies performed either at the national (Egypt) or international level ( 70 , 78 , 79 ). This observation could be attributed to the fact that older animals are exposed to infection more than young ones and aged animals get slaughtered more than young ages, since their production (calves/milk) and working capacity decrease ( 80 ).…”
Section: Discussionsupporting
confidence: 94%
“…In accordance with the studied potential variable factors, the statistical analysis revealed that the number and type of cysts, organ involved, and fertility and viability of hydatid cysts were not significantly associated with the occurrence of the of CE in camels or cattle. The present study also showed that CE were only detected in the lungs of camels, while cysts occurred mainly in the lungs of cattle and only one cyst was reported in the liver of cattle, which is consistent with several previous reports, mainly from Egypt ( 69 , 70 , 72 ). However, some previous reports revealed that the parasite exhibited single-organ involvement, although the involvement of two organs has also been recorded, which is apparently associated with the specific geographic regions and strain of the parasite ( 25 , 76 , 77 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In Al Muthanna province, the results revealed that buffalo hydatidosis recorded the highest incidence percentage (5.5%) followed by Camel (3.7%), this findings be in accordance with Abo-Aziza et al, (2019) who found that slaughtered buffalo and camel at Cairo and Giza abattoirs were highly infected with hydatidosis.…”
Section: Discussionsupporting
confidence: 84%